Evaluation of Community Pharmacists’ Knowledge and its Association with their Attitude toward Dengue Control and Management - Iqbal, Muhammad Shahid (Asian Journal of Pharmaceutics (AJP), 2020)
Background: Community pharmacists (CPs), as health-care professionals, play an important role in educating the public about dengue infection and its control and management. This study was conducted to assess the knowledge of CPs and its association with their attitude toward control and management of dengue. Materials and Methods: A cross-sectional study was conducted among CPs in using the convenience sampling technique. A newly developed and pre-validated research tool was self-administered to 205 respondents. To evaluate the knowledge of respondents, the scoring system was used and assessed using arbitrary cutoff points. Results: Of 205 respondents, 92.2% of the respondents were having the opinion that dengue is a preventable disease. The majority of respondents were able to identify the symptoms of dengue; chills (98.5%), headache (98%), pain in eyes (80%), abdominal pain (81.5%), and low backache (86.8%). Besides, 86.8% of the respondents knew that dengue infection is transmitted by the bite of Aedes mosquito. Conclusion: Although respondents showed adequate knowledge about dengue control and management, yet continuous professional development training should be frequently organized and attended to update themselves regarding the latest information that they can relay to their customers.